A Microlens Array with Different Focal Lengths Fabricated by Roll-To-Roll UV Lithography. Issue 2 (February 2018) - Ye, Huichun; Shen, Lianguan; Li, Mujun; Li, Likai
A simple, highly efficient and low cost roll-to-roll (R2R) UV imprinting lithography facility was achieved for fabricating micro-structures. Firstly, a novel microlens array with focuses distributed on a curved surface was designed and analyzed by an optical software ZEMAX. Then an ultra-precision diamond machine was applied to generate the freeform microlens array features on the master mold, and a belt-type polydimethylsiloxane (PDMS) mold with a microlens array pattern was prepared from the machined master mold. The R2R process was employed to replicate the microlens arrays, followed by an evaluation of their profiles and optical properties. Our experiments demonstrate that the applied method is reliable and efficient for producing the polymeric microlens arrays.